BPW names Raton banker as area's best (Raton Range Raton, New Mexico)
Article on Audrey Rea named as district's top businessman.
Master list item #:45
File location is in the Raton File Cabinet
Keywords: Rea, Audrey; Sunwest Bank; Local History; Biography; Award; Business woman; Raton, New Mexico